2020
DOI: 10.1002/ana.25704
|View full text |Cite
|
Sign up to set email alerts
|

The Genotypic and Phenotypic Spectrum of BICD2 Variants in Spinal Muscular Atrophy

Abstract: The bicaudal D cargo adaptor 2 (BICD2) gene encodes a conserved cargo adaptor protein required for dynein‐mediated transport. Inherited and de novo variants in BICD2 cause SMALED2 (spinal muscular atrophy lower extremity dominant 2), and a subset have recently been reported to cause severe, often lethal disease. However, a true genotype–phenotype correlation for BICD2 has not been performed, and cases described to date are scattered among at least 14 publications. In this review, we identify the characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 47 publications
(96 reference statements)
1
32
0
Order By: Relevance
“…In contrast to the milder form (SMALED2A) mostly transmitted from an affected parent, all but one mutation in severe cases occurred de novo (in the remainder case segregation analysis was not available), confirming the association of de novo mutations with the most severe forms (Koboldt et al, 2020). Despite variants in CC2 and CC3 are more often associated with severe disease than variants in CC1 (Koboldt et al, 2020), genotype–phenotype correlations are not utterly evident and other molecular mechanisms should be investigated to elucidate such a broad phenotypic spectrum.…”
Section: Discussionmentioning
confidence: 72%
“…In contrast to the milder form (SMALED2A) mostly transmitted from an affected parent, all but one mutation in severe cases occurred de novo (in the remainder case segregation analysis was not available), confirming the association of de novo mutations with the most severe forms (Koboldt et al, 2020). Despite variants in CC2 and CC3 are more often associated with severe disease than variants in CC1 (Koboldt et al, 2020), genotype–phenotype correlations are not utterly evident and other molecular mechanisms should be investigated to elucidate such a broad phenotypic spectrum.…”
Section: Discussionmentioning
confidence: 72%
“…A heterozygous missense mutation was found in the coding region of the BICD2 gene at c.1196G>A (p.Arg399His). Several studies have reported BICD2 gene mutations in patients with distal spinal muscular atrophy (SMA) [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…[75] Ref. [76] Abbreviations for Table In comparison with AO-ALS, JALS had a slower disease progression, with the exception of FUS and SOD1-associated JALS. It is also interesting to note that FUS and SOD1…”
Section: Selected Referencesmentioning
confidence: 99%
“…This domain interacts with kinesin-1, a representative motor protein, as well as dynein. According to a recent review, Cys542 is included in one of the hotspot domains of the BICD2 variants in SMA-LED [10]. They examined the relationship between variant location and clinical features.…”
Section: Discussionmentioning
confidence: 99%